IRON SHOP SENTOSA E-COMMERCE WEBSITE APPLICATION USING PHP AND MYSQL - Nurdiyanto Yusuf; Dwi Kartinah; Dewi Andryani (Asosiasi Dosen Muda Indonesia, 2022)
Information technology is an important part of human life and cannot be separated. Activities in interacting, communicating, and transacting are no longer limited by space, distance, and time. Today's website development is no longer an obstacle that is difficult to obtain. Many various websites were created, for example, a sales website (Marketplace). Marketplace is used as an intermediary between sellers and buyers. With a sales website, it makes it easier for consumers to buy goods without having to come to the store directly. The purpose of scientific writing is to make it easier for owners to provide information and to promote and sell existing products in the online store Iron shop to provide information and promote the sale of new products. only done by selling offline and customers have to come directly to the store, but with the covid-19 pandemic the store was forced to temporarily close in order to limit physical contact between sellers and buyers. Looking at these conditions, the creation of the Sentosa Iron Shop website online is the right solution and this application has been successfully created so that businesses can still run in the midst of the Covid 19 pandemic.